Implementation of the TOPSIS Method and Usability Method for Marketplace Application Based on Data Visualization (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
The rapid development of technology in online marketplaces has significantly influenced consumer shopping behavior, with applications such as Shopee, Tokopedia, Zalora, and Bukalapak leveraging advances in information and communication technology to provide faster and more efficient shopping experiences. However, frequent system disruptions often affect user satisfaction, emphasizing the need for improved information systems. This study, conducted in South Sumatra with 334 respondents, utilized questionnaire data that were processed and visualized using R, where decision-support metrics were analyzed through the TOPSIS method with equal weights and a normalized respondent data matrix calculate_topsis  function(data, weights = c(0.2, 0.2, 0.2, 0.2, 0.2)), normalized_matrix as.matrix(data responden), and the methodology integrated both the usability approach and the TOPSIS method within an R Shiny environment. The findings show that data visualization effectively applied the usability and TOPSIS methods, with usability evaluation results indicating average scores of Memorability (4.263), Satisfaction (4.186), Learnability (4.146), Efficiency (4.101), and Low Error Rate (3.749), where Memorability achieved the highest score, while the TOPSIS results highlighted Learnability as the most significant factor.